The perspective transformation in illusionistic ceiling painting of late Baroque - Szymański, Witold; Kin, Maurycy (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The following work has shown the analyses carried out in order to clarify facts necessary to understand the phenomenon of the perspective representation in the works of art in Renaissanse and late Baroque. A lot of misunderstandings have arisen on the grounds of critical work made by many theoreticians and art historians. The aim of this work was to stipulate the reasons for the conceptual and methodological fallacies. Having evaluated the methods used by illusionistic ceiling painters of late Baroque, it was possible to conduct some geometric analyses of the paintings placed on the vault of the Leopoldine Hall at the University of Wrocław.